Analisis Performa Link Stability dari Faktor Kecepatan untuk Dinamisasi Zona pada Zone Routing Protocol - Muhsin Bayu Aji Fadhillah; Radityo Anggoro; Arif Mudi Priyatno (Jurnal Rekayasa Elektrika, 2020)
Zone dynamization is carried out in the Zone Routing Protocol to allow the adaptation of the routing protocol to VANET network conditions. Zone dynamization is accomplished by periodically updating the radius within a configured time period. The value of link stability from the factors that influence network conditions is used as a reference in the radius value’s renewal process. From the test and simulation results, speed is the most dominant factor in link stability composition. Comparison between ZRP and zone dynamics against traditional ZRP shows better performance than ZRP with zonal dynamics when measured from metric analysis of packet delivery ratio, delay, and routing overhead. The increase in ZRP performance can occur because the zoning dynamics carried out make ZRP more adaptive to network conditions so that it does not work too proactively or reactively.